2011
DOI: 10.1038/nphys2111
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced polarization of Dirac valleys in bismuth

Abstract: Electrons are offered a valley degree of freedom in presence of particular lattice structures. Manipulating valley degeneracy is the subject matter of an emerging field of investigation, mostly focused on charge transport in graphene[1-4]. In bulk bismuth, electrons are known to present a threefold valley degeneracy and a Dirac dispersion in each valley. Here we show that because of their huge in-plane mass anisotropy, a flow of Dirac electrons along the trigonal axis is extremely sensitive to the orientation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
240
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(262 citation statements)
references
References 29 publications
16
240
3
Order By: Relevance
“…The existence of three anisotropic valleys offers electrons an additional degree of freedom, a subject of recent attention [2]. Here, we map the Landau spectrum by angle-resolved magnetostriction, and quantify the carrier number in each valley: while the electron valleys keep identical spectra, they substantially differ in their density of states at the Fermi level.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of three anisotropic valleys offers electrons an additional degree of freedom, a subject of recent attention [2]. Here, we map the Landau spectrum by angle-resolved magnetostriction, and quantify the carrier number in each valley: while the electron valleys keep identical spectra, they substantially differ in their density of states at the Fermi level.…”
mentioning
confidence: 99%
“…Still the unexpected hysteresis seen in the torque measurements [10], reminiscent of a first-order phase transition, remained unexplained. However, subsequent torque magnetometry studies [30] failed to reproduce this hysteresis and found no evidence of the suspected high-field phase transition.Most recently, a new experiment by Zhu et al refueled the suspicions of possible interaction effects in bismuth: the magnetoconductivity tensor in bismuth was shown to spontaneously lose the threefold rotational symmetry of the underlying lattice at low temperature and high magnetic field [2]. This behavior, which is not related to the previously reported hysteresis, is again unexpected in the non-interacting picture and suggests a type of electronic order involving the valley degree of freedom and favored by electron-electron interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the emergence of atomically thin two-dimensional (2D) crystals such as graphene and transition metal dichalcogenides (TMDC) have offered new playgrounds to explore novel electronic device concepts [4][5][6][7][8][9][10] . In addition to spin, two types of internal indices of electrons have been investigated as information carriers, namely the layer [11][12][13][14] and valley [15][16][17][18][19] degrees of freedom.…”
mentioning
confidence: 99%
“…Valleytronics is an emerging device concept [1][2][3] based on the manipulation of valley degree of freedom in certain condensed matter systems such as semiconductor quantum well [4], silicon [5], bismuth [6], diamond [7], carbon nanotube [8], graphene [9], Dirac semimetal [10], and transition-metal dichalcogenide (TMD) monolayer [11]. In these materials, electrons can populate multiple low-energy states that are well separated in momentum space, known as valley.…”
Section: Introductionmentioning
confidence: 99%